2017
DOI: 10.15850/amj.v4n2.1088
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assesment of Antibiotic Prescription for Sepsis Treatment in Intensive Care Unit at Top Referral Hospital in West Java, Indonesia

Abstract: Background: Sepsis is a common disease in intensive care unit (ICU) with high mortality rate. Administration of antibiotic has an important role to determine the outcome of sepsis patient. This study aimed to evaluate the quality of antibiotic prescription for sepsis treatment in intensive care unit (ICU). Methods: This descriptive study was conducted by retrieving data from 48 medical records of patients with sepsis, severe sepsis, and septic shock admitted to ICU Dr. Hasan Sadikin General Hospital (RSHS) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
0
0
0
4
Order By: Relevance
“…Category 0 antibiotics are indicated effective, non-toxic, appropriate in price and spectrum, dose, interval, route, and time of administration. Appropriate antibiotics use can be seen in previous research done by Adani et al (2017), who found that 35% of 118 antibiotics regimens (86 empiric therapies and 32 definitive therapies) were appropriate and rational (Category 0). This is also evident in research conducted in the ICU of Jakarta's Fatmawati General Hospital.…”
Section: The Quality Of Antibiotics In the Icu By The Gyssens Methodsmentioning
confidence: 98%
“…Category 0 antibiotics are indicated effective, non-toxic, appropriate in price and spectrum, dose, interval, route, and time of administration. Appropriate antibiotics use can be seen in previous research done by Adani et al (2017), who found that 35% of 118 antibiotics regimens (86 empiric therapies and 32 definitive therapies) were appropriate and rational (Category 0). This is also evident in research conducted in the ICU of Jakarta's Fatmawati General Hospital.…”
Section: The Quality Of Antibiotics In the Icu By The Gyssens Methodsmentioning
confidence: 98%
“…Sepsis merupakan suatu kondisi yang sering ditemui di ICU dengan persentase 6 -30%. (Adani, 2017). Suatu penelitian di Spanyol membuktikan bahwa tingkat kematian pada pasien di RS yang disebabkan Syok Septik mencapai 45,7% (Adani, 2017).…”
Section: Kasusunclassified
“…(Adani, 2017). Suatu penelitian di Spanyol membuktikan bahwa tingkat kematian pada pasien di RS yang disebabkan Syok Septik mencapai 45,7% (Adani, 2017). Sepsis diawali dengan adanya gangguan pada host misal oleh karena luka bakar dan infeksi sehingga terjadi respons inflamasi yang dimaksudkan untuk melindungi host dari kerusakan.…”
Section: Kasusunclassified
“…Adani, dkk. 27 melakukan penelitian untuk menilai kualitas peresepan antibiotik pada pasien sepsis yang dirawat di ICU RS Dr Hasan Sadikin, Bandung. Jumlah subjek yang diteliti adalah 48 pasien dengan jumlah total resep antibiotik yang dibuat adalah sebanyak 143.…”
unclassified
“…Penelitian Adani, dkk. 27 bersifat deskriptif karena tidak menilai pengaruh kualitas pemberian antibiotik tersebut terhadap perbaikan dari sepsisnya.…”
unclassified